Climbing up the greens rankings - Abd Razak, Dzulkifli (2006)
To be in the top 10 internationally is no easy feat, especially in matters as pervasive as the environment. A recent nationbynation study of environment standards jointly carried out by reputable US universities Yale and Colombia has put Malaysia in ninth place among 133 countries. It looks like the Government’s about environmental protection, as emphasized in the recent budget, is a good start. Officially named the 2006 Environmental Performance Index (EPI), it was formally released during the World Economic Forum in Davos on Jan 26. Based on a maximum scale of 100, New Zealand are tops with an overall score of 88 points, followed closely by Sweden and Finland with 87.8 and 87 points respectively.